Tag-based social image retrival system - Teo, Madeline Zhi Wei. (2012)
iAvatar is an existing Tag-based Social Image Retrieval system. At present, it allows users to search for images based on the tags. To enhance iAvatar, concept detection would be included for the tags. Concept detection helps to organize the results returned and hence allow users to find their ideal images or further refine their search words.